Trade, Productivity and semi-endogenous Growth - Christian Bauer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
We investigate the impact of incremental trade liberalization in a dynamic model of endogenous growth with heterogeneous firms and costly trade. Growth originates from horizontal specialization and the steady state productivity growth rate is positive. Innovations require costly R&D and are conducted by profit-seeking researchers. Including physical capital as a factor of production, we find that after appropriate adjustments in the production structure, previous results on the reallocation of resources and the selection of firms following trade liberalization continue to hold. We show, however, that unlike in the Melitz (2003) model, the reallocation effect does not work through increases in the factor price in production.
Keywords: F12; F13; O31; O41; 330; Productivity; entry costs; heterogeneous firms; trade Liberalization